Political Self-Identification of Russian Military Personnel in Finland in Spring 1917 - E. Yu. Dubrovskaya (Научный диалог, 2021)
The socio-psychological characteristics of the behavior of the Russian military in Finland in the initial period of the 1917 revolution were revealed, including the formation of behavioral stereotypes, new “images of the enemy”, a change in their ideas about “friends” and “foes”, and the transformation of social and moral norms. The relevance of the study is due to the need to apply a relatively new historical and anthropological approach to the study of the role of the military factor in the history of Russia and Finland. Based on the materials of the revolutionary Helsingfors and non-capital garrisons, the process of ideological and organizational self-determination of the supporters of the Socialist-Revolutionary and Bolshevik parties is considered, information about the number and the beginning of the activities of these party organizations is systematized and analyzed. The novelty of the research is seen in the fact that addressing the problem of “Revolution and man” and studying the images of “Friends”, “Foes”, “Other” in the perception of participants and eyewitnesses of events in connection with their participation in social transformations of a revolutionary time allows for the first time to get an idea of the mentality of privates and officers — the most active part of the Russian population of Finland. The author comes to the conclusion that the role of the Russian military in the events of the spring of 1917 is much more significant than was previously assumed.